PERAN KOMUNIKASI ORANGTUA DENGAN GURU DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI - Heleni Filtri; Adolf Bastian; Reswita Reswita (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2017)
Early childhood be in stages unique with progress in conjunction with the sensitive and phase golden ages.Age it is also an ideal time required for the establishment of knowledge, understanding, skill and mental attitude children.Teachers paud play an important role as the children in the development of potential through processing of different perspectives, skill and value. Value delivered teacher for interact with students.Hope, students will have the value of a character through education in paud.The value of a character to be developed for the nation include religious: character, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, the spirit of nationality, love of country, appreciate achievement, friendly, kidding, avid reader, caring environment, socially responsible, responsibility, afraid to take risks, leadership, innovative, cooperation unyielding, realistic and curiosity